Fermented Aloreña Table Olives as a Source of Potential Probiotic Lactobacillus pentosus Strains - Montoro, Beatriz Pérez; Benomar, Nabil; Lavilla Lerma, Leyre; Castillo Gutiérrez, Sonia; Gálvez, Antonio; Abriouel, Hikmate (Frontiers in Microbiology, 2016)
A collection of 31 Lactobacillus pentosus strains isolated from naturally fermented Aloreña green table olives were screened in depth in the present study for their probiotic potential. Several strains could be considered promising probiotic candidates since they showed good growth capacity and survival under simulated gastro-intestinal conditions (acidic pH of 1.5, up to 4% of bile salts and 5 mM of nitrate), good ability to auto-aggregate which may facilitate their adhesion to host cells as multiple aggregates and the subsequent displacement of pathogens. Moreover, co-aggregation of lactobacilli with pathogenic bacteria was shown with Listeria innocua, Staphylococcus aureus, Escherichia coli and Salmonella Enteriditis as good defense strategy against gut and food pathogens. Furthermore, they exhibited adherence to intestinal and vaginal cell lines, such property could be reinforced by their capacity of biofilm formation which is also important in food matrices such as the olive surface. Their antagonistic activity against pathogenic bacteria by means of acids and plantaricins, and also their different functional properties may determine their efficacy not only in the gastro-intestinal tract but also in food matrices. Besides their ability to ferment several prebiotics, the new evidence in the present study was their capacity to ferment lactose which reinforces their use in different food matrices including dairy as a dietary adjunct to improve lactose digestibility. Lactobacillus pentosus CF2-10N was selected to have best probiotic profile being of great interest in further studies. In conclusion, spontaneous fermented Aloreña table olives are considered a natural source of potential probiotic Lb. pentosus to be included as adjunct functional cultures in different fermented foods.